Attitudes Toward Mobile Advertising: A Study Of Mobile Web Display And Mobile App Display Advertising - Tri Dinh Le, Tri Dinh Le; Ho Nguyen, Bao Tran (Asian Academy of Management (AAM), 2014)
The rapid development of smartphones has resulted in the increasing use of mobile devices to deliver advertisements for products and services. Many firms in Vietnam have invested numerous resources in this field, and an in-depth understanding of mobile advertising is necessary to develop a successful mobile advertising strategy. Based on the existing literature regarding attitudes toward mobile advertising, a questionnaire was constructed to illustrate the factors affecting consumer attitudes toward advertisements on the mobile web and mobile applications. A survey of 206 participants was conducted in this study using the convenience sampling method. The findings of this study show that although many users do not have positive feelings toward advertising, they cannot ignore the importance of mobile advertising. If mobile advertisers can present credibility and entertainment in their advertisements, consumers are willing to view the ads and be influenced to buy products and services. Implications and suggestions for further studies are also provided in this study.